2017
DOI: 10.7717/peerj.3612
|View full text |Cite
|
Sign up to set email alerts
|

An updated understanding of Texas bumble bee (Hymenoptera: Apidae) species presence and potential distributions in Texas, USA

Abstract: Texas is the second largest state in the United States of America, and the largest state in the contiguous USA at nearly 700,000 sq. km. Several Texas bumble bee species have shown evidence of declines in portions of their continental ranges, and conservation initiatives targeting these species will be most effective if species distributions are well established. To date, statewide bumble bee distributions for Texas have been inferred primarily from specimen records housed in natural history collections. To im… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 60 publications
(91 reference statements)
0
12
0
Order By: Relevance
“…Our study was the first to combine citizen science data with expert-collected and historic data to examine the status of a Bumble bee species across its Canadian range (citzen science data has been used for Bumble bees in Vermont (Richardson et al 2019), Texas (Beckham and Atkinson 2017), and the UK (Lye et al 2012). The data from Bumble Bee Watch was particularly valuable as it represented 20% of the recent (2007-2016) records of B. pensylvanicus (10/50 records) and 36% of the recent B. pensylvanicus locations (8/22 sites), even with the program not having been launched until 2014.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study was the first to combine citizen science data with expert-collected and historic data to examine the status of a Bumble bee species across its Canadian range (citzen science data has been used for Bumble bees in Vermont (Richardson et al 2019), Texas (Beckham and Atkinson 2017), and the UK (Lye et al 2012). The data from Bumble Bee Watch was particularly valuable as it represented 20% of the recent (2007-2016) records of B. pensylvanicus (10/50 records) and 36% of the recent B. pensylvanicus locations (8/22 sites), even with the program not having been launched until 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Although most insect taxa require physical specimens to be collected in order for identifications to be made (Kremen et al 2011), Bumble bees can sometimes be identified to species by photos (Lye et al 2012;Richardson et al 2019;van der Wal et al 2015;Beckham and Atkinson 2017; The Xerces Society for Invertebrate Conservation, Wildlife Preservation Canada, York University, et al 2017). For example, 75% of the Bumble bee observations submitted to the iNaturalist Vermont site were identified to species through photos (Mcfarland et al 2016), and, as of January 31, 2018, 86% of all Bumble bee observations that had been submitted to Bumble Bee Watch and reviewed by an expert were identified to species (those records that were assigned a tentative identification were considered to not be identified to species, and both pending and invalid submissions (those that were not actually Bumble bees) were excluded from this analysis) (The Xerces Society for Invertebrate Conservation, Wildlife Preservation Canada, York University, et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Latreille populations of particular species have declined globally in recent decades (Williams 1986, Kearns et al 1998, Colla and Packer 2008, Bartomeus et al 2013, Beckham and Atkinson 2017). A portion of North American bumble bee species have been found to be in decline (Grixti et al 2009, Bartomeus et al 2013, Beckham and Atkinson 2017), including species once abundant in southern Ontario, Canada (Colla and Packer 2008, Colla and Dumesh 2010, Colla et al 2012). Threats to bumble bee populations include habitat loss and land-use changes, climate change, pathogen spillover from managed bees, and pesticide use (Thorp and Shepherd 2005, Colla 2006, Grixti et al 2009, Szabo et al 2012, Colla 2016).…”
mentioning
confidence: 99%
“…In the field of conservation biology, a variety of strategies have been designed, recommended, and implemented upon various wildlife populations (Ebenhard et al 1995, Primack 2008, Winfree 2010), with a focus on habitat establishment and maintenance (Cameron et al 2011, IUCN 2016, Beckham and Atkinson 2017). Primack (2008) argues that for protected areas management to be successful it must be adaptive to the results of ongoing research.…”
mentioning
confidence: 99%